Microbiota-derived β carotene is required for strobilation of Aurelia aurita by impacting host retinoic acid signaling - Nadin Jensen; Nancy Weiland-Bräuer; Cynthia Maria Chibani; Ruth Anne Schmitz (iScience)
Summary: The strobilation process, an asexual reproduction mechanism in Aurelia aurita, transitions from the sessile polyp to the pelagic medusa stage. This study explored the essential role of the microbiome in strobilation, particularly through bacterial beta carotene’s impact on the host’s retinoic acid signaling pathway. Experiments demonstrated that native polyps undergo normal strobilation while sterile polyps exhibit morphological defects. Supplementing sterile polyps with provitamin A beta carotene or the vitamin A metabolite 9-cis retinoic acid (RA) remedied these defects, underscoring their crucial role in strobilation. Transcriptional analysis revealed that beta carotene and 9-cis RA restored expression of strobilation genes in sterile polyps to native levels. Inhibition of key enzymes in the RA pathway disrupted strobilation, further confirming its importance. The expression of bacterial β-carotenoid synthesis genes in the native microbiome, contrasted with tremendously reduced expression in antibiotic-treated polyps, emphasizes the microbiome’s pivotal role in beta carotene provision, facilitating A. aurita’s strobilation through RA signaling.